1, 2-Benzisoxazole compounds: a patent review (2009 – 2014). (June 2015) - Uto, Yoshikazu
<x xml:space="preserve">Abstract</x> Introduction: Benzisoxazoles represent a class of heterocyclic compounds of great importance for the preparation of biologically active compounds. Benzisoxazoles are an important structure and some benzisoxazole-based medicines have been approved for human clinical use, including atypical antipsychotics (risperidone, paliperidone and iloperidone) and an anticonvulsant (zonisamide). Areas covered: This review puts emphasis on the recent progress in therapeutically attractive benzisoxazole derivatives especially 1, 2-benzisoxazoles, which were published in the patent literature between 2009 and 2014. As for the class of medicines, the main focus is on atypical antipsychotics and potential therapeutic treatments for other CNS disorders. This review also covers the examples of benzisoxazole-based kinase inhibitors. Moreover, novel benzisoxazoles with significant therapeutic interest are also mentioned. Expert opinion: More recent examples of structural modification of existing drugs led to the discovery of some promising benzisoxazoles for antipsychotic use. The design of multi-target ligands is important for the manipulation of pharmacological properties and safety profiles for the use of antipsychotics. Benzisoxazoles have been widely used as pharmacophores in the search for novel drug candidates in a variety of therapeutic area. It is fair to assume that the wide and frequent use of benzisoxazoles in drug discovery and development will continue into the future.